2022
DOI: 10.1515/jpm-2021-0657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SARS-CoV-2 infection on fetal umbilical vein flow and cardiac function: a prospective study

Abstract: Objectives To explore whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can affect umbilical vein blood flow (UVBF) and fetal cardiac function. Methods Prospective case-control study of consecutive pregnancies complicated by SARS-CoV-2 infection during the second half of pregnancy matched with unaffected women. Measurements of UVBF normalized for fetal abdominal circumference (UVBF/AC), atrial area (AA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In the literature, there are few Doppler and echocardiographic studies evaluating the effects of SARS-CoV-2 infection on fetal circulation. [28][29][30] Rizzo et al assessed the fetal growth velocity and fetal hemodynamics with pulsatility index of uterine, umbilical, and middle cerebral arteries Doppler in pregnancies complicated and in those not complicated by SARS-CoV-2 infection. 28 They found that pregnancies complicated by SARS-CoV-2 infection are not at higher risk of developing fetal growth restriction through impaired placental function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the literature, there are few Doppler and echocardiographic studies evaluating the effects of SARS-CoV-2 infection on fetal circulation. [28][29][30] Rizzo et al assessed the fetal growth velocity and fetal hemodynamics with pulsatility index of uterine, umbilical, and middle cerebral arteries Doppler in pregnancies complicated and in those not complicated by SARS-CoV-2 infection. 28 They found that pregnancies complicated by SARS-CoV-2 infection are not at higher risk of developing fetal growth restriction through impaired placental function.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are few Doppler and echocardiographic studies evaluating the effects of SARS‐CoV‐2 infection on fetal circulation 28–30 . Rizzo et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations